Dynamics of Land Use/Land Cover Change and its Implications for Land Degradation in Mida Woremo Watershed, North Central Ethiopia - Atile, Abrham; Asfaw, Solomon; Tekalign, Solomon (Ethiopian Journal of Social Sciences, 2021)
Land use/land cover change has been the most widely observed phenomenon in Ethiopian highlands over many decades. This study analyzed dynamics of LULCC and its implication for land degradation measures over a period of 45 years (1972 to 2017) in Mida Woremo watershed in the north central Ethiopian highlands. The study used remote sensing data including Land sat MSS (1972), Land sat TM (1986), Land sat ETM+ (2000) and Land sat OLI (2017). In addition, a total of 175 sample households residing in the watershed were selected from three kebeles namely Behera, Ketemana Dere, and Dengora using a systematic random sampling technique for questionnaire surveying, and supported it with the qualitative data gathered using focus group discussion and key informant interview. A supervised classification approach based on maximum likelihood classifier was employed to classify 1972, 1986, 2000 and 2017 images based on 238 ground truth points, and identified five major land use/land cover classes. These include cultivated land, settlement land, bare land, forest cover and bush land. A weighted average index (WAI) was used to assess farmers’ perceptions of causes of LULC changes and impacts on the biophysical environment. The results indicated that the watershed has undergone significant land use/land cover from 1972 to 2017. Over the last 45 years, the areas of cultivated, settlement and bare land were increased by an average growth rate of 5.98%, 97.06%, and 0.48% per year, respectively. These changes were at the expense of the forest and bush land covers that decreased at an average rate of 1.9% and 1.41% per year, respectively. The observed land use/land cover changes were driven by a combination of proximate and underlying driving forces. These include expansion of agriculture and settlement areas, which increased the demand for woody vegetation. This resulted in a decline in soil fertility and native vegetation, which led to land degradation. Therefore, proper land use and land management practices should be in place that take the biophysical and socio-economic set-up of the area into consideration and that ensure the livelihood of the people and maintain the ecosystem in the watershed.